2000
DOI: 10.1034/j.1399-3003.2000.16d24.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation for acute respiratory failure. Quite low time consumption for nurses

Abstract: Methods of noninvasive pressure support ventilation (NIPSV) are not always easy to apply in patients with acute exacerbations of chronic obstructive pulmonary disease (COPD).The assistance time spent by nurses in relation to ventilatory time was prospectively studied, when NIPSV was used, in a sequential mode, in COPD patients with either acute exacerbations (58 patients, group I) or postextubation hypercapnic respiratory insufficiency (42 patients, group II) in a medical intensive care unit.During the first 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…NPPV has been reported to be a time consuming procedure [42] but as with any new technique there is a learning curve and the same group have subsequently published more encouraging results [43]. A number of studies in the ICU, have shown that to start with a significant amount of time is required to establish the patient on NPPV, but this drops off substantially in subsequent days [3,44,45]. It is possible therefore that NPPV may have a much greater impact on nursing workload outside the ICU, where nurses have responsibility for a larger number of patients.…”
Section: Implications For Staffing and Trainingmentioning
confidence: 99%
“…NPPV has been reported to be a time consuming procedure [42] but as with any new technique there is a learning curve and the same group have subsequently published more encouraging results [43]. A number of studies in the ICU, have shown that to start with a significant amount of time is required to establish the patient on NPPV, but this drops off substantially in subsequent days [3,44,45]. It is possible therefore that NPPV may have a much greater impact on nursing workload outside the ICU, where nurses have responsibility for a larger number of patients.…”
Section: Implications For Staffing and Trainingmentioning
confidence: 99%
“…The protocol of sequential ventilation is appreciated by our staff and has contributed to the standardization of techniques of NIV in our ICU. 29 It has not been necessary to modify the organization of our unit since the introduction of these new techniques.…”
Section: Discussionmentioning
confidence: 99%
“…18,25 On the basis of our previous experience, we use NIV in a sequential mode. 16,[27][28][29] This mode is a discontinuous mode, with some specificity (ie, the predetermination of the duration of the ventilation sessions and of the time between the NIV sessions). One of the potential advantages of the sequential approach is a harmonious distribution of NIV sessions, plus a better acceptance and tolerance for the patients, and a better management by nursing staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deshalb gilt heute die nicht-invasive Beatmung in dieser Gruppe grundsätzlich als indiziert. Die nicht-invasive Therapie ist bei der Behandlung dieser Gruppe nicht mit einem höheren Ressourcenverbrauch als die invasive Beatmung verbunden [22].…”
Section: Nicht-invasive Beatmungunclassified